A novel direct torque control algorithm for IPMSM with minimum harmonies and torque ripples - Gulez, Kayhan.; Adam, Ali Ahmed; Pastaci, Halit (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2007)
This paper describes a new direct torque control algorithm for interior permanent-magnet synchronous motor (IPMSM) to improve the performance of hysteresis direct torque control (HDTC). The algorithm uses the output of two hysteresis controllers used in the traditional HDTC to determine two adjacent active vectors. It also uses the magnitude of the torque error and stator flux linkage position to select the switching time required for the two selected vectors. The selection of the switching time utilizes the suggested table structure, which reduces the complexity of calculation. The simulation results of this proposed algorithm show adequate dynamic torque performance and considerable torque ripples reduction as well as lower harmonic current as compared to HDTC.
Keywords: harmonic distortion; hysteresis motor control drives; permanent-magnet motors; torque control; Automation & Control Systems; Engineering